2012
DOI: 10.1002/jnr.23003
|View full text |Cite
|
Sign up to set email alerts
|

Herpes simplex virus type 1 induces nuclear accumulation of hyperphosphorylated tau in neuronal cells

Abstract: Herpes simplex virus type 1 (HSV-1) is a neurotropic virus that remains latent in host neurons. Viral DNA replication is a highly structured process in which the redistribution of nuclear proteins plays an important role. Although tau is most widely known as a microtubule-associated protein found in a hyperphosphorylated state in the brains of patients with Alzheimer's disease (AD), this protein has also been detected at other sites such as the nucleolus. Here, we establish that HSV-1 infection gives rise to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
97
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(106 citation statements)
references
References 51 publications
(56 reference statements)
9
97
0
Order By: Relevance
“…The viral particles were concentrated by ultracentrifugation at 70,000 ϫ g at 4°C and stored at Ϫ80°C. A total of 1 ϫ 10 6 PBMCs were infected by incubation with a virus suspension (ϳ1 ϫ 10 10 virions) in 1 ml of RPMI 1640 (10% fetal bovine serum [FBS]) medium in the presence of Polybrene at a final concentration of 5 g/ml and incubated for 4 h in 37°C. Cells were centrifuged for 5 min at 1,500 rpm, the supernatant was discarded, and pelleted cells were washed with fresh RPMI 1640 twice and resuspended in fresh RPMI 1640 (10% FBS).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The viral particles were concentrated by ultracentrifugation at 70,000 ϫ g at 4°C and stored at Ϫ80°C. A total of 1 ϫ 10 6 PBMCs were infected by incubation with a virus suspension (ϳ1 ϫ 10 10 virions) in 1 ml of RPMI 1640 (10% fetal bovine serum [FBS]) medium in the presence of Polybrene at a final concentration of 5 g/ml and incubated for 4 h in 37°C. Cells were centrifuged for 5 min at 1,500 rpm, the supernatant was discarded, and pelleted cells were washed with fresh RPMI 1640 twice and resuspended in fresh RPMI 1640 (10% FBS).…”
Section: Methodsmentioning
confidence: 99%
“…AK-B plays a critical role during cytokinesis and is required for histone H3 phosphorylation, chromosome biorientation, the spindle assembly checkpoint, and cytokinesis (2,3). Inhibition of AK-B activity with small molecules leads to cytokinesis failure and abnormal exit from mitosis, resulting in endoreduplication, polyploidy cells, and ultimately apoptosis (6,7). Survivin is a critical member of the CPC, which recognizes phosphorylated histone H3 threonine 3 and activates AK-B (2).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Using PHF-1 monoclonal antibody (recognizing phospho-serines 396 and 404), phosphorylated forms of Tau have been detected in the nuclei of neurons under pathological conditions, e.g. in human brain from presenile dementia with motor neuron disease (54), as well as in neuroblastoma cells treated with formaldehyde (55) or infected with herpes simplex virus type 1 (56). PHF-1 labeling had also been detected in the nuclei of the neuritogenic rat brain cell line B103 (22).…”
Section: Possible Sources Of Nuclear Aicd A␤ and Taumentioning
confidence: 99%
“…All these diseases can develop decades after the primary infection. Molecular evidences show that HSV-1 infection of neuronal and glial cells results in an increase of the intracellular levels of b amyloid (Ab), a decrease of the amyloid precursor protein and the phosphorylation of Tau protein, the main component of neurofibrillary tangles [8][9][10][11]: these are the same cellular events associated with the development of AD. Recent results have also demonstrated that the interaction between amyloid precursor protein and the HSV-1 capsid proteins [12] is essential to allow the migration of new viral particles inside infected cells.…”
mentioning
confidence: 99%